Inhibition of Protease-Activated Receptor 1 Does not Affect Dendritic Homeostasis of Cultured Mouse Dentate Granule Cells - Schuldt, Gerlind; Galanis, Christos; Strehl, Andreas; Hick, Meike; Schiener, Sabine; Lenz, Maximilian; Deller, Thomas; Maggio, Nicola; Vlachos, Andreas (Frontiers in Neuroanatomy, 2016)
Protease-activated receptors (PARs) are widely expressed in the central nervous system. While a firm link between PAR1-activation and functional synaptic and intrinsic neuronal properties exist, studies on the role of PAR1 in neural structural plasticity are scarce. The physiological function of PAR1 in the brain remains not well understood. We here sought to determine whether prolonged pharmacologic PAR1-inhibition affects dendritic morphologies of hippocampal neurons. To address this question we employed live-cell microscopy of mouse dentate granule cell dendrites in three-week old entorhino-hippocampal slice cultures prepared from Thy1-GFP mice. A subset of cultures were treated with the PAR1-inhibitor SCH79797 (1 µM; up to three weeks). No major effects of PAR1-inhibition on static and dynamic parameters of dentate granule cell dendrites were detected under control conditions. Granule cells of PAR1-deficient slice cultures showed unaltered dendritic morphologies, dendritic spine densities and excitatory synaptic strength. Furthermore, we report that PAR1-inhibition does not prevent dendritic retraction following partial deafferentation in vitro. Consistent with this finding, no major changes in PAR1-mRNA levels were detected in the denervated dentate gyrus. We conclude that neural PAR1 is not involved in regulating the steady-state dynamics or deafferentation-induced adaptive changes of cultured dentate granule cell dendrites. These results indicate that drugs targeting neural PAR1-signals may not affect the stability and structural integrity of neuronal networks in healthy brain regions.